Contraceptive effectiveness, pharmacokinetics, and safety of Sayana® Press when injected every four months: a multicenter phase 3 trial. (February 2022) - Deese, Jennifer; Brache, Vivian; Bahamondes, Luis; Salinas, Abril; Jorge, Aidelis; Veiga, Nelio; Fuchs, Rachael; Miller, Ashley; Taylor, Doug; Halpern, Vera; Dorflinger, Laneta
Summary: Background: Sayana Press® is a 3-monthly contraceptive injection approved by regulatory agencies in more than 40 countries worldwide. Existing effectiveness and pharmacokinetics (PK) data suggest that high contraceptive efficacy may be maintained if the reinjection interval of Sayana Press is extended from 3 to 4 months. Methods: We conducted a phase 3 trial at three sites in the Dominican Republic, Brazil, and Chile from September 2017 through April 2020. We enrolled 750 women at risk of pregnancy who agreed to use Sayana Press off-label every 4 months (3 treatment cycles) for 12 months. The effectiveness cohort included 710 participants randomized equally to receive injections in the abdomen or thigh. Forty additional participants received injections in the back of the upper arm for comparative PK analyses. The primary outcome was pregnancy, defined by a positive urine pregnancy test confirmed by ultrasound and/or serum human chorionic gonadotropin. Secondary outcomes included PK, safety, and acceptability. Laboratory and trial Sponsor staff were blind to injection site. This study is registered with ClinicalTrials.gov, number NCT03154125. Findings: There were no pregnancies during follow-up; the Pearl Index during 629.3 woman-years (WY) of follow-up in the primary effectiveness analysis was 0.00 (95% CI 0.00, 0.59). Pharmacokinetic profiles differed by injection site, with higher geometric mean (GM) medroxyprogesterone acetate concentrations for the abdomen than the thigh and arm. At month 8, significantly higher GM concentrations were observed in the abdomen and the thigh as compared to the arm, as well as at month 12 in the abdomen as compared to the arm. Injection site reactions were reported by 10.7% of participants. Interpretation: Both pregnancy and PK results confirm that Sayana Press is a highly effective contraceptive method when administered every 4 months. These findings may inform modification of the dosing schedule, or duration of the grace period for reinjection, or both, to reduce overall drug exposure while maintaining contraceptive efficacy. Funding: This work is made possible by the generous support of the American people through the U.S. Agency for International Development (USAID), provided to FHI 360 through Cooperative Agreement AID-OAA-A-15–00, 045, and a grant from the Gates Foundation. The contents are the responsibility of FHI 360 and do not necessarily reflect the views of USAID, the United States Government, or the Gates Foundation, nor does any mention of trade names, commercial products, or organizations imply endorsement by FHI 360, USAID, the United States Government, or the Gates Foundation.